2023
DOI: 10.1021/acsaelm.3c00062
|View full text |Cite
|
Sign up to set email alerts
|

Promising Materials and Synthesis Methods for Resistive Switching Memory Devices: A Status Review

Abstract: In recent years, the emergence of memory devices, especially resistive random-access memories (RRAM), has been a front-runner in many technological applications. This is due to its high-speed operation, structural simplicity, low power consumption, scalability potential, and high-density memory storage features. To develop an efficient and miniaturized memory device based on the resistive switching effect, it is necessary to study the range of materials and their fabrication techniques. In this review article,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 265 publications
0
8
0
Order By: Relevance
“…This could be due to either the nanobattery effect [ 32 ] or the co-existence of capacitive, resistance, and inductive effects [ 33 ]. This could be due to structural rearrangement during this type of applied voltage and the orientation of charge carriers [ 33 , 34 , 35 ]. Majumdar et al [ 36 ] suggested that a charge stored in the conjugated polymer near the electrode/polymer interface is the main contributor to charge injection and, hence, the non-zero minima in the I–V characteristic [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be due to either the nanobattery effect [ 32 ] or the co-existence of capacitive, resistance, and inductive effects [ 33 ]. This could be due to structural rearrangement during this type of applied voltage and the orientation of charge carriers [ 33 , 34 , 35 ]. Majumdar et al [ 36 ] suggested that a charge stored in the conjugated polymer near the electrode/polymer interface is the main contributor to charge injection and, hence, the non-zero minima in the I–V characteristic [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…This could be due to either the nanobattery effect [32] or the co-existence of capacitive, resistance, and inductive effects [33]. This could be due to structural rearrangement during this type of applied voltage and the orientation of charge carriers [33][34][35]. Majumdar et al The contribution of I d is due to voltage variation (first term) and capacitance variation (second term).…”
Section: Analysis Of Hysteresis In the I-v Characteristicmentioning
confidence: 99%
“…Due to their good endurance and non-volatility, memristors made of binary metal oxides such as titanium oxide [23], hafnium oxide [24,25], and tantalum oxide [26,27], are commonly referred to as resistive random access memories (ReRAMs). With the advantages of simple architecture, high-density scalability, low power consumption, good compatibility with the CMOS technique, and multi-level storage [28][29][30][31][32], ReRAMs are key candidates for the next generation non-volatile memories (NVMs) [33,34]. For NVM applications, memristors require excellent endurance and retention, good yield, on/off ratio and linearity [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…Such devices possess two stable states – (i) low conducting OFF state or high resistance state (HRS) and (ii) high conducting ON state or low resistance state (LRS). 8,13,14 This allows the application of RS devices towards memory concepts. 8 Two resistance states HRS and LRS considered as binary “0” and “1”.…”
Section: Introductionmentioning
confidence: 99%